Strategic Communication Museum Kereta Api Ambarawa (Research Manager) - Hendrikus Setya Pradhana; Djoko Setyabudi; M Bayu Widagdo; Tandiyo Pradekso (Interaksi Online, 2015)
Ambarawa train museum is a history tourism place of which is really potential to be promoted to the wide community because of having steam train that are still active and the only one in the world. But, the problem is the lack of promotion by PT KAI. Besides was related to the aspects of research, the availability of research data visitors also be the substansial problems because there is no systematic and credible data. So, this work is a form of activities that aims to back to promote Ambarawa train museum that better known in the community.In this strategic communication, research manager responsible obtain data to determine a strategy of promotion effective. Research manager were research visitors pra-event until post-event. Pra-event result of the research indicates that the knowledge about Ambarawa Train Museum (cognition) are still in figures 58 % and the attitude to visit low enough that is in figures 37 % .So to increase that aspects, during the period May to June carried out activities strategic communication “Sepoorheroes” through event, promotion and massive publication in the media. Research manager also take measurements of the success of every activity to research post-event for measuring the success of after all activities held. In doing this job, research manager to finish its appropriate duties timeline. Even though there are multiple obstacles which are external, but it was can be handled and research activities will continue to be carriedOverall, this strategic communication can be assessed as being successful, seen with the increase in the aspect of the cognition which in its implementation can be increased to 73 %, earlier from the original target 58 % to 70 % .While attitude aspect, earlier from the original target 37 % to 55 %, in its implementation can be increased as much as 66%. The whole job description research manager can also well done from the pre-event until post-event. In addition, this activity can also be admitted PT KAI to back promote their assets effectively and sustainable.